Book Review – Conflict And Change In Cambodia - Amer, Ramses (Penerbit Universiti Sains Malaysia (USM Press), 2009)
This edited volume deals with conflict and change in Cambodia and given the developments in Cambodia since the early 1970s it is a very relevant topic. The volumes deal with developments from the 1940s to the 2000s with a focus on developments in the 1990s. The contributors include established experts on Cambodia and less established scholars. The volume deals both with conflict trends, political development, and issues related to logging. The volume is structured in the following way. First, an introduction on conflict in Cambodia between 1945 and 2006 by Ben Kiernan (pp. vii– xix). Then Chapter 1 on the collapse of the "Pol Pot Regime" in early 1979 that is primarily a English language translation of an account on the experience of the Chinese diplomats to Democratic Kampuchea (DK) (pp. 1–25). Chapter 2 by David Reports is devoted to Cambodian politics 1991–1999 (pp. 26–44). Chapter 3 by Caroline Hughes also analyses Cambodian politics with a focus on the 1998 general elections and the role of international intervention (pp. 45–68). Chapter 4 by Philippe Le Billon is devoted to the issue of forest exploitation in Cambodia (pp. 69–92). Chapter 5 by Ruth Bottomley also looks at forest exploitation by analysing local responses to logging in Ratanakiri Province (pp. 93–112). Finally, in the Documents section Helen Jarvis (chapter 6) and Ben Kiernan (chapter 7) provide background information relating to the process of establishing a tribunal try leaders from the DK period (pp. 113–130).